Six new 3d-4f heterometallic coordination polymers constructed from pyrazole-bridged Cu(II)Ln(III) dinuclear units - Yang, Ting-Hai
Reactions of lanthanide chlorides, copper hydroxycarbonate and 3,5-pyrazole dicarboxylic acid (H(3)pdc) under hydrothermal conditions result in six new 3d-4f heterometallic coordination polymers with two types of structures. Compounds [CuLn(2)(pdc)(2)(Hpdc)(H2O)(4)]center dot 2H(2)O (Ln = Tb (1), Dy (2), Er (3), and Y (4) exhibit a layered porous structure, made up of Cu(II)Ln(III) di-nuclear units which are connected by protonated Hpdc(2-) ligand, while the others [Cu(3)Ln(4)(pdc)(6)(H2O)(8)] (Ln = Eu (5), Gd (6)) display a three-dimensional (3-D) framework structure, in which six Cu(II)Ln(III) di-nuclear units are cross-linked by two coordinated lanthanide atoms. The catalytic properties of 3 are investigated showing its activity and recyclability in the reaction of cyclopropanation of styrene.